Lithium manganese iron phosphate precursor, lithium manganese iron phosphate material, and preparation methods and applications of lithium manganese iron phosphate precursor and lithium manganese iron phosphate material
By using carbonate in the ethanol-water system to synthesize the precursor of ferromanganese carbonate and undergoing high-temperature calcination and ball milling, the problem of difficult particle size and poor crystallinity of the precursor of lithium manganese ferromanganese phosphate material is solved, which significantly improves the electrochemical performance and production efficiency of the material.
Patent Information
- Application Number
- CN202411766565.0
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Filing Date
- 2024-12-04
- Publication Date
- 2025-02-25
AI Technical Summary
In the existing co-precipitation method of lithium manganese iron phosphate, the particle size of the precursor is difficult to control, the crystallinity is poor, and the reaction conditions are high, which limits the electrochemical performance and large-scale production efficiency of the material.
Carbonate is used as a precipitant to synthesize the precursor of manganese ferromanganate in the ethanol-water system, and obtain the precursor of manganese oxide through high temperature calcination, and ball milling with lithium sources, phosphorus sources, and carbon sources before calcining to obtain lithium manganese ferromanganese phosphate positive electrode material.
The electrochemical properties, particle size uniformity, ion diffusion, cycle stability and thermal stability of the material are significantly improved, and the processability and large-scale production efficiency of the material are improved.
Smart Images

Figure CN119503891A_ABST
Abstract
Description
Technical Field
[0001] The present invention relates to the technical field of lithium ion batteries, and more specifically, to a lithium iron manganese phosphate precursor, a lithium iron manganese phosphate material, and preparation methods and applications thereof. Background Art
[0002] Lithium iron manganese phosphate (LiMn x Fe 1-x As a new type of cathode material, lithium iron phosphate (LMFP) has attracted widespread attention due to its excellent safety, environmental friendliness and high theoretical specific capacity. With the growing demand for lithium-ion batteries, it is particularly important to develop high-performance, low-cost cathode materials. Lithium manganese iron phosphate combines the excellent properties of manganese and iron, and has high energy density and good cycle stability. At present, the synthesis methods of LMFP are mainly divided into high-temperature solid-phase method and liquid-phase method. The high-temperature solid-phase method mainly obtains lithium manganese iron phosphate by ball milling manganese source, iron source, phosphorus source, lithium source, carbon source, etc., and then calcining. The lithium manganese iron phosphate obtained by this method usually has uneven distribution of manganese and iron, and the electrochemical performance is generally worse than that of lithium manganese iron phosphate obtained by the liquid phase method. The most common process for synthesizing lithium manganese iron phosphate by liquid phase method is coprecipitation method. The lithium manganese iron phosphate precursor is synthesized by coprecipitation method, and then the precursor is mixed with lithium source, carbon source, etc., ball milled and calcined to obtain lithium manganese iron phosphate. This method has a large synthesis volume and a relatively simple process, and can be used for large-scale commercial applications.
[0003] In the co-precipitation synthesis of lithium manganese iron phosphate, the selection and preparation of precursors are crucial. Suitable precursors can effectively improve the crystal structure, particle size and conductivity of the material, thereby improving the overall performance of the battery. At present, researchers are mainly concerned with the effects of different precursors on the performance of the final product, including their synthesis methods, heat treatment conditions and chemical composition. By optimizing the preparation process of the precursor, a more uniform manganese iron distribution, particle size distribution and better electrochemical performance can be obtained, which lays the foundation for the commercial application of lithium manganese iron phosphate.
[0004] The existing coprecipitation method mainly generates flaky structure precursors such as ferromanganese phosphate by adding manganese source and iron source solution to the phosphate system. The particle size of the precursor generated by this method is not easy to control, and the reaction requires precise control of conditions (such as pH, temperature, amount of precipitant added, etc.). At the same time, the crystallinity is relatively poor, and high-temperature dehydration may still be required to improve the crystallinity of the precursor. The coprecipitation method of the present invention uses carbonate as a precipitant to synthesize a ferromanganese carbonate precursor in an ethanol-water system. The precursor has a relatively uniform particle size and a good spherical morphology. It has low requirements for conditions during the reaction process, which is conducive to the mixed ball milling of the precursor with a lithium source, a phosphorus source, a carbon source, etc. in the subsequent process.
[0005] With the deepening of research, the prospects of lithium manganese iron phosphate positive electrode materials in battery applications are becoming increasingly broad, especially in electric vehicles and energy storage systems. Its high efficiency and long life make it an important component of future lithium-ion batteries. Summary of the invention
[0006] The primary purpose of the present invention is to provide a lithium iron manganese phosphate precursor, a lithium iron manganese phosphate material, and their preparation methods and applications. The method synthesizes an MFCO precursor by a coprecipitation method, and then calcines MFCO at a high temperature to obtain an MFO precursor. After ball milling the MFO precursor with a lithium source, a phosphorus source, and a carbon source, the sieved sample is calcined at a high temperature to obtain a lithium iron manganese phosphate positive electrode material, so that its capacity, rate performance and cycle stability are significantly improved.
[0007] In order to solve the deficiencies in the prior art, the technical solution of the present invention is as follows:
[0008] A method for preparing a lithium manganese iron phosphate precursor comprises the following steps: mixing a manganese source, an iron source, a carbonate and an antioxidant in an ethanol-water solution system to form a manganese iron carbonate MFCO material; washing, filtering and drying the product to obtain MFCO powder; and calcining the MFCO powder at a high temperature to obtain manganese iron oxide MFO.
[0009] The manganese source includes at least one of MnSO4·H2O and MnCl2; the iron source includes at least one of FeSO4·7H2O and FeCl2; the carbonate includes at least one of NH4HCO3 and (NH4)2CO3; and the antioxidant includes L-ascorbic acid.
[0010] The ratio of n(Mn):n(Fe) in the manganese source and the iron source is 0.4:0.6~0.8:0.2, preferably 0.5:0.5~0.7:0.3; the concentration of the manganese source in the ethanol-water solution system is 45-90 g / L, preferably 50-80 g / L; the concentration of the iron source in the ethanol-water solution system is 30-110 g / L, preferably 40-90 g / L; the concentration of the carbonate in the ethanol-water solution system is 5-100 g / L, preferably 10-70 g / L; the concentration of the antioxidant in the ethanol-water solution system is 0.1-3 g / L, preferably 0.5-2 g / L; the ratio of ethanol to water in the ethanol-water solution system is 1:0.5~1:2, preferably 1:0.75~1:1.5.
[0011] The temperature of high-temperature calcination of MFCO powder is 300-700° C., preferably 350-650° C.; the calcination time is 2-8 hours, preferably 3-7 hours.
[0012] The invention also provides a lithium manganese iron phosphate precursor prepared by the method.
[0013] The present invention also provides the use of the lithium iron manganese phosphate precursor in the preparation of lithium iron manganese phosphate materials.
[0014] The present invention also provides a method for preparing a lithium iron manganese phosphate material, comprising the following steps: uniformly mixing the above-mentioned lithium iron manganese phosphate precursor MFO with a lithium source, a phosphorus source, and a carbon source, ball milling, drying, and calcining at a high temperature to obtain a lithium iron manganese phosphate positive electrode material.
[0015] The lithium source includes at least one of Li2O, Li2CO3, LiOH, and LiH2PO4; the phosphorus source includes at least one of NH4H2PO4, H3PO4, and LiH2PO4; the carbon source includes at least one of glucose, chitosan, and acetylene black;
[0016] In the lithium source, n(Li):n(Mn+Fe)=1:1~1.3:1, preferably 1:1~1.2:1;
[0017] In the phosphorus source, n(P):n(Mn+Fe)=1:1~1.1:1, preferably 1:1~1.05:1;
[0018] The carbon content of the carbon source is 1-13%, preferably 2-8%;
[0019] The ball milling adopts a planetary ball mill with a rotation speed of 300-500 rpm, preferably 350-450 rpm;
[0020] After drying, sieve with a 100-400 mesh sieve, preferably a 100-200 mesh sieve;
[0021] The high temperature calcination temperature system is a two-step calcination, wherein the first step calcination temperature is 350-500°C, and the calcination time is 2-6h; the second step calcination temperature is 600-800°C, and the calcination time is 6-12h.
[0022] Furthermore, when adding lithium source, phosphorus source and carbon source for ball milling, vanadium source and titanium source are also added to obtain V-Ti co-doped lithium manganese iron phosphate;
[0023] The vanadium source includes at least one of NH4VO3, VO2(C2O4)·2H2O, and V2O5; the titanium source includes TiO2;
[0024] In vanadium source, n(V):n(Mn+Fe)=0.001:1~0.02:1; in titanium source, n(Ti):n(Mn+Fe) = 0.001:1~0.02:1.
[0025] The present invention also provides a lithium manganese iron phosphate material prepared by the method.
[0026] The present invention also provides the use of the lithium manganese iron phosphate (LMFP) material in preparing a positive electrode of a lithium ion battery, and preparing it into a positive electrode of a lithium ion battery, and further preparing it into a half-cell to detect its electrochemical performance.
[0027] The LMFP content in the positive electrode sheet is 70-90%, the conductive agent content is 5-20%, and the binder content is 5-10%.
[0028] Beneficial effects of the present invention: The spherical precursor prepared by the present invention can significantly improve the electrochemical performance, particle size uniformity, ion diffusivity, cycle stability and thermal stability of the material during the synthesis of battery materials such as lithium manganese iron phosphate. Its uniform morphology and good processability make the spherical precursor a preferred material for preparing high-performance battery materials. By using the spherical precursor, not only can the battery performance of the material be improved, but also the efficiency can be improved and the cost can be reduced in large-scale production. BRIEF DESCRIPTION OF THE DRAWINGS
[0029] Figure 1 The X-ray diffraction pattern and SEM image of MFCO prepared in Example 1.
[0030] Figure 2 The X-ray diffraction pattern and SEM image of MFO prepared in Example 1.
[0031] Figure 3 X-ray diffraction pattern and SEM image of LMFP prepared in Example 1.
[0032] Figure 4 This is a characterization diagram of the electrochemical performance of the lithium manganese iron phosphate positive electrode material in Example 1.
[0033] Figure 5 This is the X-ray diffraction pattern of the lithium manganese iron phosphate prepared in Example 4.
[0034] Figure 6 This is the SEM image of the lithium manganese iron phosphate prepared in Comparative Example 2. DETAILED DESCRIPTION
[0035] The present invention is further described below in conjunction with the accompanying drawings and specific examples, but the examples do not limit the present invention in any form. Unless otherwise specified, the reagents, methods and equipment used in the present invention are conventional reagents, methods and equipment in the art.
[0036] Example 1
[0037] A preparation method and application of a lithium iron manganese phosphate precursor of manganese iron carbonate-manganese iron oxide, comprising the following steps:
[0038] Step 1: Add 9 g NH4HCO3 to 120 mL deionized water, stir thoroughly to dissolve, then add 150 mL ethanol, stir thoroughly to mix evenly, to obtain solution 1;
[0039] Step 2: Add 2.02 g MnSO4·H2O, 2.22 g FeSO4·7H2O, and 0.2 g L-ascorbic acid into 30 mL deionized water and stir vigorously for 15 min to obtain a well-mixed ferromanganese solution;
[0040] Step 3: Add the ferromanganese solution obtained in step 2 dropwise to solution 1 obtained in step 1 at a flow rate of 10 mL / min, continue to stir vigorously for 12 h, and the reaction temperature is 30 °C;
[0041] Step 4: The solution obtained in step 3 was centrifuged, washed repeatedly with deionized water and ethanol for 3 times, and dried in an oven at 80 °C for 12 h to obtain MFCO powder;
[0042] Step 5: calcining the MFCO powder obtained in step 4 at a high temperature in an Ar atmosphere at a temperature of 600°C, a calcination time of 5 h, and a heating rate of 5°C / min to obtain MFO powder;
[0043] Step 6: Add the MFO powder obtained in step 5, 0.73 g Li2CO3, 2.3 g NH4H2PO4, and 0.43 g glucose into a ball mill, and mill in an air-tight state at 350 rpm for 8 h;
[0044] Step 7: After the mixed sample obtained in step 6 is screened through a 100-mesh sieve, the sieve-off material is calcined at high temperature in an Ar atmosphere. The temperature system is a two-stage calcination. The first-stage calcination temperature is 400°C, the calcination time is 4 h, and the heating rate is 5°C / min. The second-step calcination temperature is 650°C, the calcination time is 8 h, and the heating rate is 5°C / min. Then, it is cooled to room temperature with the furnace to obtain LiMn 0.6 Fe 0.4 PO4 powder;
[0045] Step 8: 0.21 g LiMn 0.6 Fe 0.4 PO4 pure phase powder, 0.06 g Super P and 0.03 g PVDF were ground evenly in a mortar, added into 1 mL NMP and stirred for 6 h to obtain lithium manganese iron phosphate cathode slurry;
[0046] Step 9: Coat the prepared slurry on aluminum foil with a coating thickness of 30 μm, place it in a vacuum drying oven at 100°C for 12 h, and then cut it into small disc electrodes with a diameter of 12 mm.
[0047] Step 10: Assemble the lithium-ion half-cell with the disc electrode obtained in step 9. By testing its electrochemical performance, it is found that at a current density of 0.1C, the capacity after activation reaches 155 mAh·g -1 The capacity of the battery remained at 136.9 mAh g after 100 cycles at 1C current density. -1 The capacity retention rate is 98.4%, and the capacity remains at 129 mAh g after 400 cycles. -1 , the capacity retention rate is 94.2%.
[0048] Example 2
[0049] A preparation method and application of a lithium iron manganese phosphate precursor of manganese iron carbonate-manganese iron oxide, comprising the following steps:
[0050] Step 1: Add 6 g NH4HCO3 to 120 mL deionized water, stir thoroughly to dissolve, then add 150 mL ethanol, stir thoroughly to mix, and obtain solution 1;
[0051] Step 2: Add 2.02 g MnSO4·H2O, 2.22 g FeSO4·7H2O, and 0.2 g L-ascorbic acid into 30 mL deionized water and stir vigorously for 15 min to obtain a well-mixed ferromanganese solution;
[0052] Step 3: Add the ferromanganese solution obtained in step 2 dropwise to solution 1 obtained in step 1 at a flow rate of 10 mL / min, continue to stir vigorously for 12 h, and the reaction temperature is 30 °C;
[0053] Step 4: The solution obtained in step 3 was centrifuged, washed repeatedly with deionized water and ethanol for 3 times, and dried in an oven at 80 °C for 12 h to obtain MFCO powder;
[0054] Step 5: calcining the MFCO powder obtained in step 4 at a high temperature in an Ar atmosphere at a temperature of 600°C, a calcination time of 5 h, and a heating rate of 5°C / min to obtain MFO powder;
[0055] Step 6: Add the MFO powder obtained in step 5, 0.73 g Li2CO3, 2.3 g NH4H2PO4, and 0.43 g glucose into a ball mill, and mill in an air-tight state at 350 rpm for 8 h;
[0056] Step 7: After the mixed sample obtained in step 6 is screened through a 100-mesh sieve, the sieve-off material is calcined at high temperature in an Ar atmosphere. The temperature system is a two-stage calcination. The first-stage calcination temperature is 400°C, the calcination time is 4 h, and the heating rate is 5°C / min. The second-step calcination temperature is 650°C, the calcination time is 8 h, and the heating rate is 5°C / min. Then, it is cooled to room temperature with the furnace to obtain LiMn 0.6 Fe 0.4 PO4 powder;
[0057] Step 8: 0.21 g LiMn 0.6 Fe 0.4 PO4 pure phase powder, 0.06 g Super P and 0.03 g PVDF were ground evenly in a mortar, added into 1 mL NMP and stirred for 6 h to obtain lithium manganese iron phosphate cathode slurry;
[0058] Step 9: Coat the prepared slurry on aluminum foil with a coating thickness of 30 μm, place it in a vacuum drying oven at 100°C for 12 h, and then cut it into small disc electrodes with a diameter of 12 mm.
[0059] Step 10: Assemble the lithium-ion half-cell with the disc electrode obtained in step 9. By testing its electrochemical performance, it is found that at a current density of 0.1C, the capacity after activation reaches 143.4 mAh·g -1 The capacity of the battery remains at 120.35 mAh g after 100 cycles at 1C current density. -1 , the capacity retention rate is 90.1%. ,Because a small amount of precipitant is used, the synthesis is insufficient during the precursor precipitation process.
[0060] Example 3
[0061] A preparation method and application of a lithium iron manganese phosphate precursor of manganese iron carbonate-manganese iron oxide, comprising the following steps:
[0062] Step 1: Add 9 g NH4HCO3 to 120 mL deionized water, stir thoroughly to dissolve, then add 150 mL ethanol, stir thoroughly to mix evenly, to obtain solution 1;
[0063] Step 2: Add 2.02 g MnSO4·H2O, 2.22 g FeSO4·7H2O, and 0.2 g L-ascorbic acid into 30 mL deionized water and stir vigorously for 15 min to obtain a well-mixed ferromanganese solution;
[0064] Step 3: Add the ferromanganese solution obtained in step 2 dropwise to solution 1 obtained in step 1 at a flow rate of 10 mL / min, continue to stir vigorously for 12 h, and the reaction temperature is 30 °C;
[0065] Step 4: The solution obtained in step 3 was centrifuged, washed repeatedly with deionized water and ethanol for 3 times, and dried in an oven at 80 °C for 12 h to obtain MFCO powder;
[0066] Step 5: calcining the MFCO powder obtained in step 4 at a high temperature in an Ar atmosphere at a temperature of 600°C, a calcination time of 5 h, and a heating rate of 5°C / min to obtain MFO powder;
[0067] Step 6: Add the MFO powder obtained in step 5, 0.73 g Li2CO3, 2.3 g NH4H2PO4, and 0.78 g glucose into a ball mill and mill at 350 rpm in an air-tight state for 8 h;
[0068] Step 7: After the mixed sample obtained in step 6 is screened through a 100-mesh sieve, the sieve under the sieve is calcined at high temperature in an Ar atmosphere. The temperature system is a two-stage calcination. The first step calcination temperature is 450°C, the calcination time is 4 h, and the heating rate is 5°C / min. The second step calcination temperature is 650°C, the calcination time is 8 h, and the heating rate is 5°C / min. Then, it is cooled to room temperature with the furnace to obtain LiMn 0.6 Fe 0.4 PO4 powder;
[0069] Step 8: 0.21 g LiMn 0.6 Fe 0.4 PO4 pure phase powder, 0.06 g Super P and 0.03 g PVDF were ground evenly in a mortar, added into 1 mL NMP and stirred for 6 h to obtain lithium manganese iron phosphate cathode slurry;
[0070] Step 9: Coat the prepared slurry on aluminum foil with a coating thickness of 30 μm, place it in a vacuum drying oven at 100°C for 12 h, and then cut it into small disc electrodes with a diameter of 12 mm.
[0071] Step 10: Assemble the lithium-ion half-cell with the disc electrode obtained in step 9. By testing its electrochemical performance, it is found that at a current density of 0.1C, the capacity after activation reaches 146 mAh·g -1 The capacity remains at 133.5 mAh g after 100 cycles at 1C current density. -1 The capacity retention rate is 99.44%. Excessive use of carbon source results in a thicker carbon layer on the surface of lithium manganese iron phosphate, which in turn hinders the diffusion of lithium ions, resulting in a lower capacity of the material.
[0072] Example 4
[0073] A preparation method and application of a V-Ti co-doped lithium manganese iron phosphate positive electrode material, comprising the following steps:
[0074] Step 1: Add 9 g NH4HCO3 to 120 mL deionized water, stir thoroughly to dissolve, then add 150 mL ethanol, stir thoroughly to mix evenly, to obtain solution 1;
[0075] Step 2: Add 2.02 g MnSO4·H2O, 2.22 g FeSO4·7H2O, and 0.2 g L-ascorbic acid into 30 mL deionized water and stir vigorously for 15 min to obtain a well-mixed ferromanganese solution;
[0076] Step 3: Add the ferromanganese solution obtained in step 2 dropwise to solution 1 obtained in step 1 at a flow rate of 10 mL / min, continue to stir vigorously for 12 h, and the reaction temperature is 30 °C;
[0077] Step 4: The solution obtained in step 3 was centrifuged, washed repeatedly with deionized water and ethanol for 3 times, and dried in an oven at 80 °C for 12 h to obtain MFCO powder;
[0078] Step 5: calcining the MFCO powder obtained in step 4 at a high temperature in an Ar atmosphere at a temperature of 600°C, a calcination time of 5 h, and a heating rate of 5°C / min to obtain MFO powder;
[0079] Step 6: Add the MFO powder obtained in step 5, 0.73 g Li2CO3, 2.3 g NH4H2PO4, 0.43 g glucose, 0.008 g NH4VO3, and 0.004 g TiO2 into a ball mill and mill at 350 rpm in an air-tight state for 8 h;
[0080] Step 7: After the mixed sample obtained in step 6 is screened through a 100-mesh sieve, the sieve-off material is calcined at high temperature in an Ar atmosphere. The temperature system is a two-stage calcination. The first-stage calcination temperature is 400°C, the calcination time is 4 h, and the heating rate is 5°C / min. The second-step calcination temperature is 650°C, the calcination time is 8 h, and the heating rate is 5°C / min. Then, it is cooled to room temperature with the furnace to obtain LiMn 0.6 Fe 0.4 PO4 powder;
[0081] Step 8: 0.21 g LiMn 0.6 Fe 0.4 PO4 pure phase powder, 0.06 g Super P and 0.03 g PVDF were ground evenly in a mortar, added into 1 mL NMP and stirred for 6 h to obtain lithium manganese iron phosphate cathode slurry;
[0082] Step 9: Coat the prepared slurry on aluminum foil with a coating thickness of 30 μm, place it in a vacuum drying oven at 100°C for 12 h, and then cut it into small disc electrodes with a diameter of 12 mm.
[0083] Step 10: Assemble the disc electrodes obtained in step 9 into a lithium-ion half-cell.
[0084] In order to verify the electrochemical performance of the lithium iron manganese phosphate cathode material that inhibits manganese dissolution, it was further used as a cathode material for lithium-ion batteries: the prepared lithium iron manganese phosphate cathode material was dissolved in N-methylpyrrolidone with a conductive agent and a binder to prepare a slurry, which was coated on aluminum foil and vacuum dried to assemble a lithium-ion battery as an electrode material. By testing its electrochemical performance, it was found that at a current density of 0.1C, the capacity after activation reached 155.3 mAh·g -1 The capacity of the battery remained at 130.2 mAh g after 100 cycles at 1C current density. -1 , the capacity retention rate is 90.8%.
[0085] Comparative Example 1
[0086] Step 1: Dissolve 2.22 g FeSO4·7H2O, 2.02 g MnSO4·H2O and 0.2 g L-ascorbic acid in 30 mL deionized water, and stir to dissolve under an Ar atmosphere to prepare solution A;
[0087] Step 2: Dissolve 2.3 g NH4H2PO4 in 120 mL deionized water and 150 ml ethanol until completely dissolved to prepare solution B;
[0088] Step 3: Add solution A to solution B at a flow rate of 10 mL / min, stir for 30 min, and then use a constant flow pump to pump concentrated ammonia water at a flow rate of 3 mL / min until the pH is adjusted to 6-7, and keep warm at 70°C for 3 h, and then let it stand for 6 h;
[0089] Step 4: After aging, the solution was centrifuged, washed with water and ethanol for 3 times respectively, and vacuum dried at 80°C for 12h to obtain ammonium manganese iron phosphate precursor material;
[0090] Step 5: calcining the ammonium manganese iron phosphate precursor material at 600° C. in an Ar atmosphere for 3 h to remove crystal water and bound water;
[0091] Step 6: The ammonium manganese iron phosphate precursor material from which the crystal water was removed was mixed with 0.73 g Li2CO3, 0.43 g glucose, and 10 mL ethanol and wet-milled for 6 h at a ball mill speed of 350 rpm;
[0092] Step 7: Dry the mixture obtained in step 6, pass it through a 400-mesh sieve, and send the sieved material for roasting;
[0093] Step 8: Place the sieved mixed material into a tube furnace for calcination in an argon atmosphere at 400 °C for 3 h, then at 650 °C for 6 h, and cool naturally to room temperature to obtain a lithium manganese iron phosphate positive electrode material;
[0094] Step 9: Take out 0.21 g LiMn from the lithium iron manganese phosphate positive electrode material obtained in step 8 0.6 Fe 0.4 PO4 pure phase powder, 0.06 g Super P and 0.03 g PVDF were ground evenly in a mortar, added into 1 mL NMP and stirred for 6 h to obtain lithium manganese iron phosphate cathode slurry;
[0095] Step 10: Coat the prepared slurry on aluminum foil with a coating thickness of 30 μm, place it in a vacuum drying oven at 100°C for 12 h, and then cut it into small disc electrodes with a diameter of 12 mm.
[0096] Step 11: Assemble the lithium-ion half-cell with the disc electrode obtained in step 10. By testing its electrochemical performance, it is found that at a current density of 0.1C, the capacity after activation reaches 143.37 mAh·g -1 After 100 cycles at 1C current density, the capacity remains at 115.85 mAh g -1 The capacity retention rate is 89%; the capacity remains at 108.07 mAh g after 200 cycles. -1 The capacity retention rate is 83.02%. It can be seen that the effect of lithium manganese iron phosphate positive electrode material prepared by phosphate system co-precipitation method is far inferior to that of carbonate system.
[0097] Comparative Example 2
[0098] A preparation method and application of a lithium iron manganese phosphate precursor of manganese iron carbonate-manganese iron oxide, comprising the following steps:
[0099] Step 1: Add 9 g NH4HCO3 to 120 mL deionized water, stir thoroughly to dissolve, then add 150 mL ethanol, stir thoroughly to mix evenly, to obtain solution 1;
[0100] Step 2: Add 2.02 g MnSO4·H2O, 2.22 g FeSO4·7H2O, and 0.2 g L-ascorbic acid into 30 mL deionized water and stir vigorously for 15 min to obtain a well-mixed ferromanganese solution;
[0101] Step 3: Add the ferromanganese solution obtained in step 2 dropwise to solution 1 obtained in step 1 at a flow rate of 10 mL / min, continue to stir vigorously for 12 h, and the reaction temperature is 30 °C;
[0102] Step 4: The solution obtained in step 3 was centrifuged, washed repeatedly with deionized water and ethanol for 3 times, and dried in an oven at 80 °C for 12 h to obtain MFCO powder;
[0103] Step 5: Add the MFCO powder obtained in step 4, 0.73 g Li2CO3, 2.3 g NH4H2PO4, and 0.43 g glucose into a ball mill, and mill in an air-tight state at 350 rpm for 8 h;
[0104] Step 6: After the mixed sample obtained in step 5 is screened through a 100-mesh sieve, the sieve-off material is calcined at high temperature in an Ar atmosphere. The temperature system is a two-stage calcination. The first-stage calcination temperature is 400°C, the calcination time is 4 h, and the heating rate is 5°C / min. The second-stage calcination temperature is 650°C, the calcination time is 8 h, and the heating rate is 5°C / min. Then, it is cooled to room temperature with the furnace to obtain LiMn 0.6 Fe 0.4 PO4 powder;
[0105] Step 7: 0.21 g LiMn 0.6 Fe 0.4 PO4 pure phase powder, 0.06 g Super P and 0.03 g PVDF were ground evenly in a mortar, added into 1 mL NMP and stirred for 6 h to obtain lithium manganese iron phosphate cathode slurry;
[0106] Step 8: Coat the prepared slurry on aluminum foil with a coating thickness of 30 μm, place it in a vacuum drying oven at 100°C for 12 h, and then cut it into small disc electrodes with a diameter of 12 mm.
[0107] Step 9: Assemble the disc electrode obtained in step 9 into a lithium-ion half-cell. By testing its electrochemical performance, it was found that at a current density of 0.1C, the capacity after activation reached 79.47 mAh·g -1 After 100 cycles at 1C current density, the capacity remains at 73.16 mAh g -1 , the capacity retention rate is 98.5%. Although the capacity retention rate is high, the initial capacity is extremely low and the performance is poor.
[0108] pass Figure 6It can be seen that the LMFP prepared by using MFCO as a precursor and directly ball-milling with lithium source, phosphorus source and carbon source has an irregular structure, the surface is wrapped, and the phenomenon of hardening occurs. In contrast, the surface of LMFP prepared by MFO has more pores, which is conducive to electrolyte infiltration and lithium ion migration.
Claims
1. A method for preparing a lithium manganese iron phosphate precursor, characterized in that: A manganese source, an iron source, a carbonate and an antioxidant are uniformly mixed in an ethanol-water solution system to form a manganese iron carbonate MFCO material, and the product is washed, filtered and dried to obtain MFCO powder; the MFCO powder is calcined at a high temperature to obtain manganese iron oxide MFO.
2. The method for preparing a lithium iron manganese phosphate precursor according to claim 1, characterized in that: The manganese source includes at least one of MnSO4·H2O and MnCl2; the iron source includes at least one of FeSO4·7H2O and FeCl2; the carbonate includes at least one of NH4HCO3 and (NH4)2CO3; the antioxidant includes L-ascorbic acid; The ratio of n(Mn):n(Fe) in the manganese source and the iron source is 0.4:0.6~0.8:0.2, preferably 0.5:0.5~0.7:0.3; the concentration of the manganese source in the ethanol-water solution system is 45-90 g / L, preferably 50-80 g / L; the concentration of the iron source in the ethanol-water solution system is 30-110 g / L, preferably 40-90 g / L; the concentration of the carbonate in the ethanol-water solution system is 5-100 g / L, preferably 10-70 g / L; the concentration of the antioxidant in the ethanol-water solution system is 0.1-3 g / L, preferably 0.5-2 g / L; the ratio of ethanol to water in the ethanol-water solution system is 1:0.5~1:2, preferably 1:0.75~1:1.
5.
3. The method for preparing a lithium iron manganese phosphate precursor according to claim 1, characterized in that: The temperature of high-temperature calcination of MFCO powder is 300-700° C., preferably 350-650° C.; the calcination time is 2-8 hours, preferably 3-7 hours.
4. The lithium iron manganese phosphate precursor prepared by the method according to any one of claims 1 to 3.
5. Use of the lithium iron manganese phosphate precursor according to claim 4 in the preparation of lithium iron manganese phosphate materials.
6. A method for preparing lithium manganese iron phosphate material, characterized in that: The method comprises the following steps: uniformly mixing the lithium iron manganese phosphate precursor MFO described in claim 4 with a lithium source, a phosphorus source and a carbon source, ball milling, drying and calcining at a high temperature to obtain a lithium iron manganese phosphate positive electrode material.
7. The preparation method according to claim 6, characterized in that: The lithium source includes at least one of Li2O, Li2CO3, LiOH, and LiH2PO4; the phosphorus source includes at least one of NH4H2PO4, H3PO4, and LiH2PO4; the carbon source includes at least one of glucose, chitosan, and acetylene black; In the lithium source, n(Li):n(Mn+Fe)=1:1~1.3:1, preferably 1:1~1.2:1; In the phosphorus source, n(P):n(Mn+Fe)=1:1~1.1:1, preferably 1:1~1.05:1; The carbon content of the carbon source is 1-13%, preferably 2-8%; The ball milling adopts a planetary ball mill with a rotation speed of 300-500 rpm, preferably 350-450 rpm; After drying, sieve with a 100-400 mesh sieve, preferably a 100-200 mesh sieve; The high temperature calcination temperature system is a two-step calcination, wherein the first step calcination temperature is 350-500 °C, and the calcination time is 2-6 h; the second step calcination temperature is 600-800 °C, and the calcination time is 6-12 h.
8. The preparation method according to claim 6 or 7, characterized in that: When adding lithium source, phosphorus source and carbon source for ball milling, vanadium source and titanium source are also added to obtain V-Ti co-doped lithium manganese iron phosphate; The vanadium source includes at least one of NH4VO3, VO2(C2O4)·2H2O, and V2O5; the titanium source includes TiO2; In vanadium source, n(V):n(Mn+Fe)=0.001:1~0.02:1; in titanium source, n(Ti):n(Mn+Fe) = 0.001:1~0.02:
1.
9. The lithium iron manganese phosphate material prepared by the method according to any one of claims 6 to 8.
10. Use of the lithium iron manganese phosphate material according to claim 9 in preparing a positive electrode of a lithium ion battery.